Erythropoietin does not reduce plasma lactate, H+, and K+ during intense exercise. Issue 6 (30th December 2014) - Nordsborg, N. B.; Robach, P.; Boushel, R.; Calbet, J. A. L.; Lundby, C.
Abstract : It is investigated if recombinant human erythropoietin (rHuEPO) treatment for 15 weeks ( n  = 8) reduces extracellular accumulation of metabolic stress markers such as lactate, H +, and K + during incremental exhaustive exercise. After rHuEPO treatment, normalization of blood volume and composition by hemodilution preceded an additional incremental test. Group averages were calculated for an exercise intensity ∼80% of pre‐rHuEPO peak power output. After rHuEPO treatment, leg lactate release to the plasma compartment was similar to before (4.3 ± 1.6 vs 3.9 ± 2.5 mmol/min) and remained similar after hemodilution. Venous lactate concentration was higher ( P  < 0.05) after rHuEPO treatment (7.1 ± 1.6 vs 5.2 ± 2.1 mM). Leg H + release to the plasma compartment after rHuEPO was similar to before (19.6 ± 5.4 vs 17.6 ± 6.0 mmol/min) and remained similar after hemodilution. Nevertheless, venous pH was lower ( P  < 0.05) after rHuEPO treatment (7.18 ± 0.04 vs 7.22 ± 0.05). Leg K + release to the plasma compartment after rHuEPO treatment was similar to before (0.8 ± 0.5 vs 0.7 ± 0.7 mmol/min) and remained similar after hemodilution. Additionally, venous K + concentrations were similar after vs before rHuEPO (5.3 ± 0.3 vs 5.1 ± 0.4 mM). In conclusion, rHuEPO does not reduce plasma accumulation of lactate, H +, and K + at work rates corresponding to ∼80% of peak power output.